Relationship between emotional intelligence and workload towards job performance among primary school teachers in Mata Ayer, Perlis - Nabil Fikri, Abdullah (2019)
Nowadays, teachers claimed that there are suffering stress in doing their job. Teachers also claimed that they have a high workload in their job because of the new policy that being implemented by the government. The purpose of this research is to examine the relationship between emotional intelligence and workload towards job performance among primary school teachers in Mata Ayer, Perlis. A total of 84 teachers are participated in the study. The questionnaire 27 items that have used five-point Likert scale. Researcher use Statistics Package for Social Science (SPSS) version 25 for analyses the data from the questionnaires. The obtained data were analyzed using descriptive analysis and multiple regression. The results showed that emotional intelligence have a positive and significant relationship towards job performance. Meanwhile, workload was found did not have significant relationship towards job performance. In order to achieve high job performance, emotional intelligence skills need to be developed and improved by teachers through consistent and systematic approach. Lastly, limitations of the study and suggestions for future research were also highlighted in the study.